Physical and Cup Quality Attributes of Arabica Coffee (Coffea arabica L.) Varieties Grown in Highlands of Amhara Region, Northwestern Ethiopia - Melese Wale Mengistu; Melkamu Alemayehu Workie; Abrar Sualeh Mohammed (International Journal of Agronomy, 2020)
Coffee is the second most traded commodity worldwide after oil both in terms of volume and value. The study was therefore initiated to evaluate the quality of highland coffee varieties grown in the region. For this purpose, coffee bean samples of the varieties Merdacheriko, Yachi, Wush Wush, Buno wash, 741, 7440, Ababuna, and Ageze were collected from trees which were grown in Adet and Woramit Agricultural Research Centers in RCBD with three replications. Physical (length and width of coffee beans, 100 bean weight, screen sizes, and raw quality) and cup quality (aromatic intensity, aromatic quality, acidity, astringency, bitterness, body, flavor, overall standard, and total cup quality) parameters, as well as total coffee quality, were evaluated by a team of certified panelists at Jimma Agricultural Research Center. The results depicted significant variations in physical quality parameters of coffee varieties, while the cup and total qualities of coffee varieties in WARC and in AARC were similar. In WARC, Buno wash, Wush Wush, and Ababuna coffee varieties showed better physical quality in terms of 100 bean weight, bean length, bean width, and screen size, while varieties Buno wash and Wush Wush showed better physical quality only in terms of 100 bean weight and bean length in AARC. Cup quality of coffee varieties grown in WARC ranged from 48.16% to 51.33% while that of coffees grown in AARC ranged from 45.00% to 50.83%. Total coffee quality in WARC was at the range from 85.50 to 89.33% while in AARC from 81.66 to 87.83%, which is within the standard of Ethiopian Commodity Exchange for coffee. All the tested varieties of Arabica coffee can be therefore used to produce coffee in both study areas and areas with similar agroecology of the Amhara Region, Ethiopia. Further research on the yield performance of the coffee varieties is also recommended.